The Role of Notary in Making the Deed on Inheritance of Land Rights - Muhammad Rofik Kanna; Achmad Sulchan; Taufan Fajar Riyanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This writing aims to determine the process of dividing the inheritance of land rights by a notary and theoretical analysis of the role of a notary in making a deed of inheritance of land rights. The role of a Notary in the transfer of land rights based on inheritance is very large, where every transfer of land rights must be proven by a deed made by and before a Notary so that the deed he makes has binding legal force. The researcher used a legal research method with a normative juridical approach, the research specifications used were descriptive analysis, the data source came from secondary data. Methods of data collection were conducted through interviews, library research, and document studies. This writing was analyzed qualitatively by using the analytical knife of legal certainty theory and Islamic justice theory. The results showed that the process of distributing inheritance rights to land carried out by a Notary, namely the parties (heirs) together faced the Notary in the presence of 2 (two) witnesses. Both parties bring the files that are the formal requirements and the material requirements that have been determined. Theoretical analysis of the role of the notary in making the deed of distribution of inheritance rights to land is carried out with justice, so it is fair not justice. This is similar to Islamic justice theory. Basically the concept of justice in Islam is not